Reconstruction of Legal Norms on the Criminal Offense of Bank Account Trading for Online Gambling: An Islamic Criminal Law Perspective - Muhamad Abdul Kholik; Rena Zulfaidah; Ananda Dewi Maharani; Ismail Ismail; Nisa Afifah (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the Indonesian criminal law system should be able to encompass all actors within the chain of online gambling crimes, including account sellers as facilitators of financial transactions. However, the Criminal Code (KUHP), the Electronic Information and Transactions Law (UU ITE), and banking regulations have not yet criminalized the practice of buying and selling bank accounts as an independent offense. Law enforcement still relies on Articles 55–56 of the KUHP, which are weak in proving mens rea, resulting in a normative gap and a low deterrent effect amid the rise of digital gambling. This study aims to analyze the practice of buying and selling bank accounts in online gambling, examine criminal liability from the perspective of Islamic law through the concept of ta‘zīr al-mu‘īn ‘alā al-ma‘ṣiyah, and formulate an integrative normative reconstruction. The method used is juridical-normative with a conceptual-comparative approach, analyzing primary and secondary legal materials through qualitative-descriptive methods. The results indicate that account sellers can be classified as mu‘īn (facilitators of sin) who violate the objectives of Islamic law (maqāṣid al-syarī‘ah), particularly ḥifẓ al-māl (protection of property) and ḥifẓ al-dīn (protection of religion). A new legal provision is recommended to explicitly criminalize such acts, with a maximum penalty of 5 years imprisonment or a fine of up to IDR 500 million, in order to close legal gaps and respond to digital crime.